EFEKTIFITAS PENGGUNAAN APLIKASI AGEMARA TERHADAP MENINGKATKAN KEMAMPUAN MEMBACA PERMULAAN SISWA KELAS II SEKOLAH DASAR - Putri Imatriyani Sholekhah; Sekar Dwi Ardianti; Rani Setiawaty (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2025)
This research aimed to determine the significant effect of elementary students’ beginning reading skill before and after the use of the AGEMARA application. The research employed a quantitative method with a “One Group Pretest–Posttest Design”. The research subjects were the grade II students of State Elementary School 2 Jobokuto (SD Negeri 2 Jobokuto). The data were collected through a beginner reading test to examine students’ beginning reading skills before and after the use of the media. The data were analyzed using a paired sample t-test to identify whether there was a significant difference before and after the use of the AGEMARA application. In addition, the N-Gain score test was conducted to analyze the improvement obtained by the students after using AGEMARA. The findings indicated a difference in the level of students’ beginning reading skills that were showed by the paired sample t-test result which showed a Sig value of 0.000 ≥ 0.10. Furthermore, an improvement in students’ beginning reading skills after the treatment using the AGEMARA application demonstrated by the N-Gain score of 0.18, if this value is viewed using the N-Gain Score classification category, the value obtained was 0.20 ≥ 0.2 and can be stated in the “Medium” category.